JEAN DE LÉRY E A ESCRITA DA HISTÓRIA Uma heterologia calvinista - Medeiros, Christian Brially de (2012)
The inauguration of a human eye the tupinamba Indian, here's what we found in Jean de Léry (1534-1611), a Huguenot theologian and missionary who brings in Brazilian lands in the sixteenth century with the purpose of assisting in the establishment of a French colony and preach the gospel, so that the French were here, as the Indians. The traveler in his History of a Voyage made to the Land of Brazil, otherwise called America presents a human gaze of the Other that, moreover, it also presents itself as an opportunity to understand the same. The reasons that build this perspective is analyzed in this work, from concept heterology proposed by Michel de Certeau. Our thesis states that this hermeneutics of the Other in Jean de Léry is determined by the system of Calvinist theological thought. The circularity of hermeneutics French traveler is subject to Scripture, her part, she returns. The heterology proposed by Jean de Léry constitutes a science Other built from the Calvinist theological system of thought.